Mental Health Stigma and its Implications for Access to Care - Soni, Hitesh (Shodh Sagar Journal for Medical Research Advancement, 2024)
Those individuals who are interested in receiving appropriate mental health treatment and who desire to do so face a significant impediment in the form of the stigmatisation of mental illness, which is pervasive and deeply embedded in society. The purpose of this study is to investigate the multifaceted nature of stigma that is associated with mental health and the significant impact that stigma has on an individual's capacity to seek treatment for mental health issues. The purpose of this article is to shed light on the origins, symptoms, and consequences of stigma connected with mental health difficulties by providing a comprehensive overview of past research with the purpose of providing information. There is a complicated interaction between individual, cultural, and social factors that results in the stigma that is associated with dealing with mental health issues. As a result of the fact that stigmatising attitudes and beliefs contribute to the propagation of stereotypes, discrimination, and social isolation, they deter a significant proportion of individuals from seeking assistance for concerns that are associated with their mental health. Those who are affected by mental health conditions as a consequence are more likely to have a delay in treatment, a worsening of their symptoms, and a loss in their general wellbeing as a consequence of this.